A novel unified model for laminated composite beams. (15th April 2020) - Nguyen, Trung-Kien; Nguyen, Ba-Duy; Vo, Thuc P.; Thai, Huu-Tai
Abstract: Based on fundamental equations of the elasticity theory, a novel unified beam model is developed for laminated composite beams. In this model, the displacement field is selected in a unified form which can be recovered to that of existing shear deformation beam theories available in the literature. Based on Lagrange's equations, the governing equations of the present theory are derived. They are then solved for deflections, stresses, natural frequencies and critical buckling loads of composite beams under different boundary conditions and lay-ups by using the Ritz approach with novel hybrid trigonometric functions. Various examples are also presented to verify the accuracy and generalization of the present theory, as well as investigate the influences of fibre angle on the behaviour of composite beams under different boundary conditions and lay-ups.